2020
DOI: 10.3390/sym12101618
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Hidden Mixture Transition Distribution Model in Clustering Few but Long Continuous Sequences: An Illustration with Cognitive Skills Data

Abstract: In accordance with the theme of this special issue, we present a model that indirectly discovers symmetries and asymmetries between past and present assessments within continuous sequences. More specifically, we present an alternative use of a latent variable version of the Mixture Transition Distribution (MTD) model, which allows for clustering of continuous longitudinal data, called the Hidden MTD (HMTD) model. We compare the HMTD and its clustering performance to the popular Growth Mixture Model (GMM), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Here, the article proposed by Mohamed Yusuf Hassan is particularly interesting, because not only is the MTD model applied to a domain in which it has never been used before (respiratory infections), but moreover, the model is compared to other statistical tools; it is shown that it proves to be a very good competitor of a more classical model such as the SARIMA model [6]. Finally, the article by Zhivko Taushanov and Paolo Ghisletta proposes another innovative application using cognitive skills data [7]. Here again, a comparison is proposed with two types of GMM models.…”
Section: Contributionsmentioning
confidence: 99%
“…Here, the article proposed by Mohamed Yusuf Hassan is particularly interesting, because not only is the MTD model applied to a domain in which it has never been used before (respiratory infections), but moreover, the model is compared to other statistical tools; it is shown that it proves to be a very good competitor of a more classical model such as the SARIMA model [6]. Finally, the article by Zhivko Taushanov and Paolo Ghisletta proposes another innovative application using cognitive skills data [7]. Here again, a comparison is proposed with two types of GMM models.…”
Section: Contributionsmentioning
confidence: 99%